Can Heaven Justify Horrendous Moral Evils? A Postmortem Autopsy - Lancaster-Thomas, Asha (Religions, 2023)
James Sterba has recently constructed a new and compelling logical problem of evil that rejects Plantinga’s free-will defense and employs the concept of significant freedom and the Pauline Principle to demonstrate an incompatibility between the existence of horrendous evil and the God of classical monotheism. In response, Jerry L. Walls, among others, has claimed that the doctrine of heaven can explain why God is justified in permitting horrendous evils in the world—an argument known as the afterlife theodicy. In this article, I explore this line of defense against Sterba’s logical problem of evil. I suggest that if the afterlife theodicy is to be effective, it must accept non-speciesist, strong universalism; deny or explicate divinely informed prior consent; reject an elective model of forgiveness; discard postmortem libertarian free will; and explain why God values libertarian free will in earthly life but not in the afterlife.